1993
DOI: 10.1177/0265407593104002
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Ties that Bind: Affective Expression and Perceived Conflict in Parent adolescent Interactions

Abstract: The purpose of this observational study was (1) to examine the process of parent-adolescent relationship change across puberty, and (2) to examine the relationship between affective expression in interactions and perceived relationship conflict. Data were collected on 85 intact families with adolescents in grades 5 to 9 (n = 44 males, 41 females). Each parent and adolescent took part in two 8-minute conversations one about an activity they reported enjoying together and one about a disagreement or area of conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Nevertheless, it has been shown that the speci c issues measured in the present study (adolescents' relationships with parents) may be measured validly by self-report measures. For example, adolescents' self-report measures of relationships with parents were consistently associated with similar behavioural measures recorded by observers (Flannery, Montemayor, Eberly, & Torquati, 1993). Similarly, self-report hardiness scores were found to correlate with objective measures of health (e.g.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, it has been shown that the speci c issues measured in the present study (adolescents' relationships with parents) may be measured validly by self-report measures. For example, adolescents' self-report measures of relationships with parents were consistently associated with similar behavioural measures recorded by observers (Flannery, Montemayor, Eberly, & Torquati, 1993). Similarly, self-report hardiness scores were found to correlate with objective measures of health (e.g.…”
Section: Discussionmentioning
confidence: 64%
“…In an effort to discover the mechanisms accounting for this increased incidence, researchers have examined the myriad of developmental changes that accompany the transition into adolescence. One notable change is an increase in the frequency and intensity of negative affect (Flannery et al, 1993;Larson and LampmanPetraitis, 1989;Larson and Richards, 1991), which can act as a precursor to depression (Klein et al, 2002). This increase correlates with pubertal status (Flannery et al, 1993) and age (Larson and Richards, 1991) and appears to vary according to the social context.…”
mentioning
confidence: 99%
“…One notable change is an increase in the frequency and intensity of negative affect (Flannery et al, 1993;Larson and LampmanPetraitis, 1989;Larson and Richards, 1991), which can act as a precursor to depression (Klein et al, 2002). This increase correlates with pubertal status (Flannery et al, 1993) and age (Larson and Richards, 1991) and appears to vary according to the social context. In particular, Larson and Richards (1991) reported that the increase was observed in the context of interactions with parents, but did not characterize the time spent with friends.…”
mentioning
confidence: 99%
“…Examining macrotimescale flexibility and inertia would also elucidate whether low flexibility or high inertia predicts psychopathology during certain developmental periods. For example, because dyadic affective flexibility peaks in early adolescence (e.g., , inertia might be at its lowest, but, given the increase in intensity of negative affect in parent-adolescent relationships (Flannery et al 1993;Laursen et al 1998), both inertia and rigidity may heighten and yield problematic symptomatology for youth.…”
Section: Additional Timescalesmentioning
confidence: 99%